1995
DOI: 10.1128/jvi.69.9.5278-5286.1995
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of mutations contributing to the temperature sensitivity of the Sabin 1 vaccine strain of poliovirus

Abstract: The temperature-sensitive and attenuated phenotypes of the Sabin type 1 vaccine strain of poliovirus result from numerous point mutations which occurred in the virulent Mahoney virus parent. One of these mutations is located in a 3D polymerase (3D pol ) codon (U-62033C, Tyr-733His) and is involved in attenuation in common mice (M. Tardy-Panit, B. Blondel, A. Martin, F. Tekaia, F. Horaud, and F. Delpeyroux, J. Virol. 67: [4630][4631][4632][4633][4634][4635][4636][4637][4638] 1993). This mutation also appears to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…This finding suggests that there may be communication pathways linking the Sabin sites, and modifications at these sites may act cooperatively to change RdRp function; previous MD simulations of WT RdRp have also indicated that the motions of the ␣-helix containing Tyr-73 are anti-correlated with the motions of motif D containing Thr-362 (42). The Sabin amino acid substitutions may also contribute to different RdRp functions; the Y73H substitution has been shown to interfere with RdRp initiation (62), K250E may interfere with protein structure and/or long-range interactions with RNA through changes to electrostatic interactions, and T362I, in addition to its role in RdRp fidelity shown here, has been shown to contribute to temperature sensitivity of the Sabin I vaccine (59). The other Sabin substitutions may even compensate for the effects observed here with T362I.…”
Section: Discussionmentioning
confidence: 86%
“…This finding suggests that there may be communication pathways linking the Sabin sites, and modifications at these sites may act cooperatively to change RdRp function; previous MD simulations of WT RdRp have also indicated that the motions of the ␣-helix containing Tyr-73 are anti-correlated with the motions of motif D containing Thr-362 (42). The Sabin amino acid substitutions may also contribute to different RdRp functions; the Y73H substitution has been shown to interfere with RdRp initiation (62), K250E may interfere with protein structure and/or long-range interactions with RNA through changes to electrostatic interactions, and T362I, in addition to its role in RdRp fidelity shown here, has been shown to contribute to temperature sensitivity of the Sabin I vaccine (59). The other Sabin substitutions may even compensate for the effects observed here with T362I.…”
Section: Discussionmentioning
confidence: 86%
“…This is supported by the identification of a VP3-Phen91 mutation, near a promoter interface in poliovirus Sabin-3 strain, which affects poliovirus assembly sufficiently to act as an attenuation determinant [45]. In addition, the latter study showed that known ts producing mutations located in the 3D pol-coding region and 3 0 -UTR of poliovirus Sabin-1 [46,47] could be transferred to EV71 producing similar ts phenotypes. This is a clear indication that single mutations may be sufficient to change growth and neurovirulence phenotypes in wild-type EV71 isolates.…”
Section: Molecular Genetics Of Virulencementioning
confidence: 80%
“…Identification of Amino Acids Determined Temperature Sensitivity. Previous studies revealed that two amino acids in 3D region (His-73 and Ile-362) were determinants of temperature sensitivity (Bouchard et al 1995;Georgescu et al 1995). A sequence analysis of 3D region of PJ156/CAV-17 showed that amino acid in 3D-73 and -362 were Tyr and Ile, respectively, similar with the parental CAV-17 sequence.…”
Section: Generation Of Temperature-resistant Pj156/cav-17mentioning
confidence: 84%
“…Previous studies revealed that mutations in the 5'NCR, base 2438 of VP3, bases 2741, and 2795 of VP1, base 6203 of 3Dpol, and base 7441 of the 3'NCR were associated with phenotypic reversion of the temperature sensitivity of PV, particularly Sabin 1 strain (Bouchard et al 1995). In addition, two amino acids in 3D region (His-73 and Ile-362) were determinants for temperature sensitivity of PV Sabin 1 (Georgescu et al 1995). Although it is reported that a chimeric plasmid from cDNA clones of poliovirus and coxsackievirus produces a recombinant virus that is temperature-sensitive (Semler et al 1986), it is not known whether those amino acids affect the temperature sensitivity of CAV, including CAV-17.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation